Report of the Irrigation and Power Team on Chambal Project (Madhya Pradesh and Rajasthan) - Planning Commission (Planning Commission, 1958)
The Project has undergone several changes before it was officially sanctioned in 1954 though the work was started on it in 1953. The changes in the sites of the Gandhi Sagar Dam and the Kotah Barrage, the brief history of which is given in Appendix If of the Report, necessitated several alterations with the result that it had not been possible to finalise the Project report till recently. In the circumstances, the Chambal Project was deprived of the benefits of thorough investigations in the preconstruction stage. It was also not possible in view of this, to draw up precise schedules of materials, technical personnel, machinery and equipment at the time of the commencement of the Project and this has inevitably and naturally left its mark.
Report on Chambal Project (Madhya Pradesh and Rajasthan)
Government of India Planning Commission
Keywords: Administration; Features of Design and construction; Management of irrigation and utilization of water; Power generation; Works needing urgent attention; Recommendations and observations and comments; Utilization of trained personnel and materials; Phasing of construction; Progress made in construction; Ensure economy; Efficiency in the construction.